Thrombin Stimulates Inositol Phosphate Accumulation and Prostacyclin Synthesis in Human Endothelial Cells from Umbilical Vein but Not from Omentum - Carter, A J; Eisert, W G; Müller, T H (Thrombosis and Haemostasis, 1989)
We have compared the effects of thrombin on the accumulation of inositol phosphates and the synthesis of prostacyclin in cultured human endothelial cells from umbilical vein and the microvasculature of omentum. Active human thrombin induced a dose-dependent accumulation of inositol phosphates and a concomitant synthesis of prostacyclin in endothelial cells from human umbilical vein. However, thrombin at all concentrations tested was unable to stimulate inositol phosphate accumulation and prostacyclin synthesis in microvascular endothelial cells from human omentum. Bradykinin was able to stimulate these effects in both types of cell. These results demonstrate that although inositol phosphate turnover is an initial event associated with prostacyclin synthesis in endothelial cells, there are differences in the way microvascular endothelial cells respond to thrombin.
Keywords: Endothelial cells; Thrombin; Inositol phosphates; Prostacyclin